Nintedanib improves cardiac fibrosis but leaves pulmonary vascular remodelling unaltered in experimental pulmonary hypertension. Issue 2 (18th July 2018) - Rol, Nina; de Raaf, Michiel A; Sun, Xiaoqing Q; Kuiper, Vincent P; da Silva Gonçalves Bos, Denielli; Happé, Chris; Kurakula, Kondababu; Dickhoff, Chris; Thuillet, Raphael; Tu, Ly; Guignabert, Christophe; Schalij, Ingrid; et al.
Abstract: Aims: Pulmonary arterial hypertension (PAH) is associated with increased levels of circulating growth factors and corresponding receptors such as platelet derived growth factor, fibroblast growth factor and vascular endothelial growth factor. Nintedanib, a tyrosine kinase inhibitor targeting primarily these receptors, is approved for the treatment of patients with idiopathic pulmonary fibrosis. Our objective was to examine the effect of nintedanib on proliferation of human pulmonary microvascular endothelial cells (MVEC) and assess its effects in rats with advanced experimental pulmonary hypertension (PH). Methods and results: Proliferation was assessed in control and PAH MVEC exposed to nintedanib. PH was induced in rats by subcutaneous injection of Sugen (SU5416) and subsequent exposure to 10% hypoxia for 4 weeks (SuHx model). Four weeks after re-exposure to normoxia, nintedanib was administered once daily for 3 weeks. Effects of the treatment were assessed with echocardiography, right heart catheterization, and histological analysis of the heart and lungs. Changes in extracellular matrix production was assessed in human cardiac fibroblasts stimulated with nintedanib. Decreased proliferation with nintedanib was observed in control MVEC, but not in PAH patient derived MVEC. Nintedanib treatment did not affect right ventricular (RV) systolic pressure or total pulmonary resistance index in SuHx rats and had no effects on pulmonary vascular remodelling. However, despite unaltered pressure overload, the right ventricle showed less dilatation and decreased fibrosis, hypertrophy, and collagen type III with nintedanib treatment. This could be explained by less fibronectin production by cardiac fibroblasts exposed to nintedanib. Conclusion: Nintedanib inhibits proliferation of pulmonary MVECs from controls, but not from PAH patients. While in rats with experimental PH nintedanib has no effects on the pulmonary vascular pathology, it has favourable effects on RV remodelling.